Algorithm, Aphorism, and Alternatives - Gustafson, Erik J. (New Explorations, 2023)
The following paper revisited Gozzi Jr.’s (2002) probing of algorithmic and aphoristic thinking. Drawing on literature from media ecology, surveillance studies, and new materialism, the following paper argued that dichotomies between algorithmic and aphoristic thought reinforce a cartesian dualism between self and object that makes impossible meaningful discourse about, and subsequent alteration of, our data- driven technologies and policies. In his endorsement of the aphorism, Gozzi Jr. (2002) was careful to note that aphoristic thinkers did often employ algorithmic thinking in practice and principle, though the current data-driven nature of society drives a wedge deeper between these two modes of thought. Instead, a mode of thinking for the 21st century requires competency in both aphoristic thinking and ideation and algorithmic comprehension and application. Thus, the present paper explicated what is meant by the term “algorithmic society,” outlined aphoristic and algorithmic modes of thought, and offered an alternative perspective that incorporated algorithmic and aphoristic thinking in a cyclical and systemic manner in order to create space for continued discourse.